2009
DOI: 10.3139/146.110042
|View full text |Cite
|
Sign up to set email alerts
|

Strain-hardening behaviour of AZ31 magnesium alloys

Abstract: The in-plane tensile behaviour of rolled sheets of the magnesium alloy AZ31 was investigated in both an H24 state and an aged state. Whereas the very high initial strain-hardening rate decreases monotonically with strain for the H24 samples, the annealed structure exhibits a striking increase in the strain-hardening rate. To explain this phenomenon, the occurrence of sessile dislocations associated with a secondary (pyramidal) slip is proposed. The absence of increasing hardening for the H24 state is supposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…σ plots for the annealed rolled AZ31 magnesium alloy sheets deformed in both RD and TD [27]. Balík et al [30] have concluded that such deformation behaviour can be connected with the activity of double prismatic slip.…”
Section: Discussionmentioning
confidence: 99%
“…σ plots for the annealed rolled AZ31 magnesium alloy sheets deformed in both RD and TD [27]. Balík et al [30] have concluded that such deformation behaviour can be connected with the activity of double prismatic slip.…”
Section: Discussionmentioning
confidence: 99%
“…2d and 3d). The upcoming decrease in the AE count rates is connected with the decrease in the free path of the moving dislocation owing to an increase in dislocation density resulting in the strain hardening of the material [39,40].…”
Section: General Findings During Pre-compression and Reverse Tensile mentioning
confidence: 99%
“…In an earlier paper [4], rather sharp initial increases (lifts) of strain hardening coecient were revealed for in-plane tension of AZ31 sheets and well-aged conditions. In the usual stress-strain curves, these lifts correspond to short S-shaped periods ≤ 1% of the strain followed by a parabolic part characteristic of a continuous slip mode.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the present paper is to extend the analysis of early deformation stages of rolled sheets of AZ31 that was introduced in [4]. Further tensile tests and measurements of the texture after deformation were conducted.…”
Section: Introductionmentioning
confidence: 99%